2020
DOI: 10.15761/crt.1000322
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Evaluation of Angiogenesis in Warts

Abstract: Objectives: Angiogenesis is a key event in tumour growth. An infection with human papillomavirus (HPV) typically leads to benign tumours, such as warts (papillomas) on the skin and mucous membranes. The role of angiogenesis in skin warts is yet to be established. Materials and methods:The present work evaluates the hypothesis that the development of skin warts is associated with alterations in the dermal vascularisation (dermal microvessel density/mm 2 , MVD). Seventeen cases of cutaneous warts and eight cases… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…CD105 is important for assessing neoangiogenesis and is highly expressed in activated endothelial cells. It has been shown that CD105-positive vessels are newly formed and fragile; hence, they can easily rupture or bleed [ 29 ].…”
Section: Literature Search Strategy and Yielded Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CD105 is important for assessing neoangiogenesis and is highly expressed in activated endothelial cells. It has been shown that CD105-positive vessels are newly formed and fragile; hence, they can easily rupture or bleed [ 29 ].…”
Section: Literature Search Strategy and Yielded Resultsmentioning
confidence: 99%
“…Furthermore, CD105 has an affinity for active cells in the vascular endothelium. Therefore, it has been described as a suitable neoangiogenic marker [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%